A study on edutainment framework for M-learning - Suki, , Norbayah Mohd; Eshaq, ., Ahmad Rafi M; Rao, , G. S. V. Radha Krishna (2006)
This research measures the potential of mobile content in learning to increase users' tacit knowledge development. Concentration is given on the effectiveness of incorporating game-based learning into mobile technology as a new edutainment instructional model. A comparative study on selected mobile content platforms is carried out to examine to what extents the usage of game are being applied in learning from the users perspective. A survey is conducted on the users' reaction on the impacts of mobile technology and its content impact on the traditional and conventional learning method. A perceptual test is carried out to support the survey. This research proposes a framework on how mobile technology and its content could shape the learning in future. With the emergence of new tools and media, mobile content is suggested as a powerful means to increase tacit knowledge via the exploration of interactivity, multimedia and 3d animation for creative edutainment and communication in the future.